1995
DOI: 10.1002/micr.1920160108
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brachial plexus lesions in the adult: Indications and results

Abstract: While numerous situations may produce a traumatic brachial plexus palsy, these injuries are characteristic of young adults aged 18 -20 who have had a motorcycle accident. '-lo Lesions can be situated at any level from the base of nerve roots to the divisions of the brachial plexus in the axillary region, and several types of lesions can be differentiated: Supraclavicular lesions at the root level (75% of cases) Infra-and retroclavicular lesions of secondary trunks and of terminal branches (25% of cases)The les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
8

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 7 publications
1
36
0
8
Order By: Relevance
“…Interestingly, drawing from both the literature [11][12][13] and our previous results, 3 we also estimate that, on average, roughly three in four (78%) of patients with total palsy have at least one nonavulsed root. Therefore, it seems plausible to suggest that, in total palsy, pain is related to the presence of a nonavulsed root, rather than avulsion of the lower roots, which has occurred in 100% of these patients.…”
Section: Painmentioning
confidence: 79%
“…Interestingly, drawing from both the literature [11][12][13] and our previous results, 3 we also estimate that, on average, roughly three in four (78%) of patients with total palsy have at least one nonavulsed root. Therefore, it seems plausible to suggest that, in total palsy, pain is related to the presence of a nonavulsed root, rather than avulsion of the lower roots, which has occurred in 100% of these patients.…”
Section: Painmentioning
confidence: 79%
“…In almost 80 % of patients with complete brachial plexus palsy, at least one root is not avulsed [6,7]. Hence, it is believed that brachial plexus pain is not generated by avulsed roots, but rather by non-avulsed roots.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicated that a better outcome could be attained by coapting grafts distal to the lateral or posterior cord to achieve more distal coaptation near the distal objective (i.e., the musculocutaneous nerve). On the other hand, Alnot [3] and Terzis [55] have reported that the use of nerve grafts is more successful when coapting nerve grafts distal to the peripheral nerve rather than distal to the proximal plexus elements (i.e., the cords). At this point most of the nerve fibers would not be lost in fortuitous reinnervation, which would result in achievement of the desired goal.…”
Section: Discussionmentioning
confidence: 99%